الأنماط الجرمية المنتشرة في محافظة اللاذقية وخصائص مرتكبيها "دراسة ميدانية للجرائم المرتكبة في السجن المركزي بمدينة اللاذقية - عقيـل أديـب; برقـاوي هناء; اسماعيل رنـدا (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
الجريمة ظاهرة اجتماعية مورست قديماً، ولاتزال تمارس، وطالما وجد الإنسان وجدت المشكلة ووجد الانحراف، ومما لا شك فيه أن معرفة أسباب الجريمة تساعد بوضوح في الإسهام في تضييق نطاقها, والحد من آثارها الضارة في المجتمع. والجريمة في المجتمعات ليست مطلقة وإنما نسبية يختلف تحديدها من مجتمع لآخر وفق عاداته, ونظمه, وقوانينه. والإنسان هو محور ودعامة أي نهضة، وهو العقل المدبر الذي يوجهها, وينير لها الطريق, والقائد الذي يقود مسيرتها، والنموذج الأخلاقي الذي يضفي عليها المثل العليا, والأخلاق النبيلة. لذا كانت بناء الإنسان السوي أملاً غالياً تتطلع إليه الإنسانية, وترى فيه الهدف الأسمى الذي يهون في سبيله كل صعب, وتذلل من أجله كل عقبة. وما أكثر المشكلات الاجتماعية التي تحيد بالإنسان عن جادة الصواب, فتؤدي به إلى انحراف في سلوكه, وبالتالي إلى تفكيك دعائم الحياة الآمنة! ولا شك أن الفلسفة الحديثة للنظام العقابي في أي دولة متقدمة تستهدف إصلاح المذنب, وتقويمه, والنهوض بمستوى قيمه ومفاهيمه مما يساعد في تغيير شخصيته, وتغيير نظرته العامة للحياة، فيستطيع العودة إلى زمرة المجتمع مواطناً شريفاً, وعاملاً نافعاً منتجاً. Crime is a social phenomenon which exists from the ancient times and still goes on till these days, because where a human lives there are problems and deviance. And no doubt that finding out the reasons which lie behind crimes obviously contributes in narrowing their spread and limiting their harmful effects on society. Crimes in societies are not absolute but rather relative and differ from a community to another based on its traditions, systems and rules . A human is the base upon which any renaissance lies, because he’s the brain which redirects and lights its way, besides being its leading and ethical model which provides it with its ethics and noble manners. That’s why reforming a Syrian becomes the achievement that humanity mostly looks up to and thinks of him as the highest goal that deserves any sacrifice. There are a lot of social problems which confuse a human and lead him away from the good behavior, which accordingly dissolve the bases for a safe life. No doubt that the modern philosophy for the penal system in any modern country aims to evaluate the guilty person and try to reform him and to raise the level of his concepts and values in order to modify his character and change his general view of life so it makes him again "an honest good citizen" and "a useful productive worker" in society.